The Infleuence of Total Quality Management (Continues Improvement and Training) on the Public and Private HealthcareInstitutions Effectiveness in Yemen - et.al, Abobakr S. S. Ahmed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: This research was developed for the purpose of finding out the impact of total quality management (continuous improvement and training) on the public and private healthcare institutions' effectiveness in Yemen. Design/ Method/ Approach: The descriptive-analytical approach was used in this study; it is one of the most used methods in the study of social and human phenomena, and because it fits the phenomenon under study. It also examines an existing phenomenon or issue from which information can be answered to answer study questions, without the intervention of the researcher. Findings: regression test has been used to conduct statistical analysis from the primary data. Several tests have been conducted for the collected data. The main results found that that there is a positive and significant relationship between continuous improvement and the healthcare public and private institutions' effectiveness in Yemen. Also, there is a positive and significant relationship between training and the healthcare public and private institutions' effectiveness in Yemen. Recommendation: In the health sector, it is always necessary to remember that the essence of the service is the human. It should be kept in mind that human life will be harmed when a mistake is made. The lack of statistical data and information sharing increases the likelihood of errors occurring repeatedly. Managers should eliminate fear, communication barriers, and situations that make it difficult for people to do business and make arrangements where the feeling of success is experienced together with continuous improvement.